Pattern of Parenteral Antimicrobial Prescription among Pediatric ‎Patients in Al-Watani Governmental Hospital in Palestine - Ansam Sawalha; Ghada Al-Bishtawi; Laila Al-Khayyat; Nidal Jaradat; Rowa Al-Ramahi; Waleed Sweileh (My University, 2006)
Objective: No studies were carried out in Palestine to investigate the prescribed antimicrobial agents in hospitalized pediatric patients. The objective of this study was to evaluate and therapeutically analyze the pattern of parenteral antimicrobial prescriptions among pediatric patients in Al-Watani Government Hospital in Palestine. Such audit will be of great value to clinicians and health policy makers. Material and Methods: Data on antimicrobial prescribing were collected for 30 consecutive days for all pediatric patients admitted to Al-Watani government hospital. Data on antimicrobial prescribing were entered and analyzed using Statistical Package for Social Sciences (SPSS) program. Analysis was done for age, sex, diagnosis, site of infection, number of antimicrobial agents given, how many times the drug regimen has been changed and the frequency of individual drug use. Results: Three hundred and forty pediatric patients were admitted to Al-Watani government hospital during the study period. Gastroenteritis was the most common cause of hospitalization, while upper respiratory tract infection (URTI) was the most common cause of parenteral antimicrobial agent administration. Two hundred and ten (61.8%) patients received parenteral antimicrobial agents while 16 (4.7%) received both parenteral and oral antimicrobial agents. Single antimicrobial agent was prescribed for (50.6%) patients. Cefuroxime was the main single antimicrobial agent used; it was administered to 70/226 (31%) patients. Conclusion: Treatment patterns used for most patients were nearly according to current empiric therapeutic recommendations. However, improving the availability of rapid diagnostic methods to differentiate between viral and bacterial infections is suggested to reduce empiric therapy numbers by antimicrobial agents so as to decrease chance for drug resistance.

الهدف: لم تجر أية دراسة لوصف المضادات الحيوية عند الأطفال المدخلين للمستشفى في فلسطين من قبل. الهدف من هذه الدراسة هو التدقيق والتحليل العلاجي لنمط الوصف الدوائي للمضادات الحيوية التي تعطى عن طريق الحقن الوريدي في قسم الأطفال في المستشفى الوطني الحكومي في فلسطين. وسيكون هذا التدقيق ذا قيمة كبيرة لواضعي السياسة الصحية والعملين في مجالها. المادة ووسائل البحث: تم تجميع البيانات عن المضادات الحيوية المستخدمة في علاج الأطفال الذين أدخلوا المستشفى الوطني الحكومي خلال ثلاثين يوما، و إدخال و تحليل البيانات عن طريق برنامج SPSS. اشتمل التحليل على عمر المريض وجنسه والتشخيص المرضي و موقع الالتهاب وعدد المضادات الحيوية المستخدمة وعدد المرات التي تم فيها تغيير برتوكول العلاج وعدد مرات استخدام الدواء وعدد جرعات الدواء المستخدمة. النتائج: في ذلك الشهر، أدخل المستشفى 340 مريضا. وحقن 210 (%61.8) من المرضى بمضادات حيوية، بينما عولج 16(%4.7) مريضا بمضادات حيوية عن طريق الفم و الحقن معا. تلقى (76.1%) 172 مريضا مضادا حيويا واحدا، وكان cefuroxime هو المضاد الحيوي الأكثر استخداما في هذه الحالات، و قد وصف ل 70/226 (31%) مريضاً. كانت التهابات الجهاز الهضمي هي السبب الرئيسي لدخول المرضى إلى المستشفى، بينما احتلت التهابات الجهاز ا لتنفسي العلوية المرتبة الأولى لأنها كانت السبب الرئيسي لإعطاء المضادات الحيوية عن طريق الحقن. الاستنتاج: كانت الأنماط المتبعة في العلاج مقاربة لبروتوكولات العلاج الحديثة المتبعة عالميا. إن البحث عن طرق أفضل لتشخيص الالتهابات الفيروسية والبكتيرية والتمييز بينهما هو من التوصيات المقترحة لتقليل استخدام المضادات الحيوية في بداية العلاج، وتوجيه المضاد الحيوي المناسب - نتيجةً لذلك - للكائن الدقيق المعزول من المريض و المسبب للمرض، و تقليل مقاومة الكائنات الدقيقة للمضادات الحيوية.
نمط استخدام حقن المضادات الحيوية في قسم الأطفال في المستشفى الوطني الحكومي -‏فلسطين